THE EFFECT OF FEEDING TANNIN-PROTECTED FISH MEAL ON THE INCREASE OF BODY WEIGHT AND BODY SIZE OF LOCAL SHEEP - Rohimat, agung (Unpad Press, 2025)
Protein protection using tannins is expected to increase utilization efficiency protein in ruminants. .This research aims to determine the effect of adding tannin-protected fish meal to the ration on the growth of body weight and body size of local sheep. The method used was an experiment with a Completely Randomized Design (CRD) followed by the Duncan test. There were four ration treatments and five replications. P0 = Basal feed (80% field grass + 20% tofu dregs), P1 = Basal feed + 4% fish meal, P2 = Basal feed + 2% tannin-protected fish meal, P3 = Basal feed + 4% tannin-protected fish meal. The result of statistical analysis concluded that adding tannin-protected fish meal for a period of 42 days had no significant effect on increasing body weight and body size of local sheep. Keywords : sheep, fish meal, tannin, body weight, body size